Emergence of nano S&T in Germany: network formation and company performance - Thomas Heinze (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2006)
This article investigates the emergence of nano S&T in Germany. Using multiple longitudinal data sets, we describe the complete set of research institutions and companies that entered this science-based technology field and the development of their inter-organisational networks between 1991 and 2000. We demonstrate that the co-publication network is a core-periphery structure in which some companies were key players at an early stage of field formation, whereas later universities and other extra-university institutes took over as the central drivers of scientific progress. Further differentiating among types of firms and research organisations, we find that in the co-patent network collaboration is most intense between high-technology firms and use-inspired basic research institutes. While many companies co-patent with several universities or other public institutes, some succeed in establishing almost exclusive relationships with public research units. It is shown that co-patent and co-publication ties are most effective at strengthening the technological performance of firms, that multiple interaction channels increase company performance, and that companies benefit from collaborating with scientifically central universities and institutes.
urn:nbn:de:0011-n-454616
Keywords: 330; nanotechnology; network analysis; company performance; public research sector; innovation system; science industry cooperation; Germany; Nanotechnologie; Forschungskooperation; Industrielle Forschung; Business Network; Unternehmensentwicklung; Deutschland